2015
DOI: 10.1007/s11095-015-1722-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterisation of Non-Deamidated Acidic Variants of Erwinia chrysanthemi L-asparaginase Using Small-Angle X-ray Scattering and Ion-Mobility Mass Spectrometry

Abstract: IEX data for biopharmaceuticals such as ErA should be thoroughly characterised, as the most common modifications, such as deamidation, may be absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, such isolated variants often contain more than one PTM, so care must be taken during interpretation of the results. Multiple, orthogonal analytics may be required to fully understand the changes present in the protein, such as recently reported for L‐asparaginase …”
Section: Impact Of Deamidation On Protein Biopharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such isolated variants often contain more than one PTM, so care must be taken during interpretation of the results. Multiple, orthogonal analytics may be required to fully understand the changes present in the protein, such as recently reported for L‐asparaginase …”
Section: Impact Of Deamidation On Protein Biopharmaceuticalsmentioning
confidence: 99%
“…Multiple, orthogonal analytics may be required to fully understand the changes present in the protein, such as recently reported for L-asparaginase. 80 Deamidation may be expected to have a deleterious impact on biopharmaceutical protein function. Certainly this appears to be the case for many proteins including recombinant human stem cell factor.…”
Section: Impact Of Deamidation On Protein Biopharmaceuticalsmentioning
confidence: 99%
“…Structural changes were compared with those revealed by ion mobility analysis. Panels A and B were adapted with permission from figures from references 54 and 57, respectively.…”
Section: Figurementioning
confidence: 99%
“…Overall the results show that IMS-MS is a useful tool for monitoring protein stability upon ligand binding and it is also suggested that such combined measurements could be very useful in the pursuit of drug development. In other studies, IMS-MS measurements (Figure 3A) were combined with small angle x-ray scattering (SAXS) spectroscopy to study enzymatic variants and provided structural information that was not typically obtained for ion exchange chromatography isolates [54]. Other experiments combined fluorescence spectroscopy and gas-phase dimer-induced fluorescence self quenching with IMS-MS measurements to study the structures of small peptides and ubiquitin [55].…”
Section: Introductionmentioning
confidence: 99%
“…60 A further example of pH-induced changes to HOS was studied in the anti-leukaemic enzyme Erwinia chrysanthemi L-asparaginase (ErA). Minor HOS changes were detected using SAXS and IM-MS. 68 Initially, these conformational changes were detected simply as fully-functional acidic variants using ion-exchange chromatography (IEX), and were assumed to be deamidated enzyme variants. Further investigation using tryptic-digest LC-MS showed that deamidation was absent, but SAXS ( Fig.…”
Section: Relationship Between Biopharmaceutical Manufacture and Hos Cmentioning
confidence: 99%